ASSESSMENT OF DIABETES KNOWLEDGE USING DIABETES KNOWLEDGE QUESTIONNAIRE AMONG PEOPLE WITH TYPE 2 DIABETES MELLITUS - Dussa, Kanchana; S, Parimalakrishnan; Sahay, Rakesh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Type 2 diabetes is a metabolic disorder, the effective management of which requires not only medication use but also patient diabetes knowledge for adopting necessary life-style modifications. Those with greater knowledge of diabetes are expected to maintain better glycemic control. Assessment of the diabetes knowledge using diabetes knowledge questionnaire (DKQ) among Type 2 diabetes mellitus (T2DM) subjects and its correlation with glycated hemoglobin (HbA1c) levels. A cross-sectional study was conducted at the outpatient clinics Department of Endocrinology, Osmania Hospital. Subjects with T2DM of either gender, between the age of ≥18 years and <85 years, capable of understanding and completing questionnaires were included. Subject who were not willing to participate and not capable of understanding and completing the questionnaires were excluded. DKQ adapted for South Asian population was used to assess patient's diabetes knowledge. DKQ score was based on 18 point scale with 0.2 and 18 points, with ≥9 score were considered as satisfactory score. Associations between DKQ scores and HbA1c and duration of diabetes were measured. 80 subjects with T2DM were enrolled in this study. 74 completed study and 6 not completed questionnaires due to various reasons. Mean duration of diabetes 6.5±5.9 years and DKQ score mean was 5.14±2.205. HbA1c levels (n=66) mean was 8.76±1.862. DKQ score did not show significant correlation with HbA1c levels but correlated with disease duration. Level of diabetes knowledge among study population was low. Majority of people were illiterate, and level of education was less among study population. Improving diabetes knowledge of people with diabetes might allow achieving better glycemic control. Involving a clinical pharmacist with endocrinologist might achieve this objective of improving patient knowledge of diabetes when followed longitudinally. Keywords: Questionnaire, collaborative care, diabetes knowledge level, diabetes education, Barrier.